2023
DOI: 10.1186/s12933-023-01884-7
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-visit HbA1c variability is associated with aortic stiffness progression in participants with type 2 diabetes

Abstract: Background Glycemic variability plays an important role in the development of cardiovascular disease (CVD). This study aims to determine whether long-term visit-to-visit glycemic variability is associated with aortic stiffness progression in participants with type 2 diabetes (T2D). Methods Prospective data were obtained from 2115 T2D participants in the National Metabolic Management Center (MMC) from June 2017 to December 2022. Two brachial-ankle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Emerging evidence suggests that blood glucose variability could exert a more significant impact on aortic stiffness. Individuals with diabetes, particularly those with poorly managed blood glucose levels and significant variability, face an elevated risk of aortic stiffness and related cardiovascular complications [45,46]. Therefore, emphasizing the control of blood glucose fluctuations through comprehensive diabetes management strategies is pivotal for mitigating the risk of aortic stiffness and enhancing cardiovascular health outcomes among individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that blood glucose variability could exert a more significant impact on aortic stiffness. Individuals with diabetes, particularly those with poorly managed blood glucose levels and significant variability, face an elevated risk of aortic stiffness and related cardiovascular complications [45,46]. Therefore, emphasizing the control of blood glucose fluctuations through comprehensive diabetes management strategies is pivotal for mitigating the risk of aortic stiffness and enhancing cardiovascular health outcomes among individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…T2D participants were recruited from the National Metabolic Management Center (MMC) at Ruijin Hospital, Shanghai Jiao Tong University School of Medicine [ 26 28 ]. A total of 4831 T2D participants with either DKD or DR follow-up data were included between June 2017 and June 2023.…”
Section: Methodsmentioning
confidence: 99%
“…In this project, people who never smoked or successfully stopped smoking for over one year were classified as ‘ideal smoking’ status. More elaborate definitions and collection methods for covariates were provided in previous publications [ 26 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a nationally representative cross-sectional study conducted in mainland China with 173,642 participants in 2018, the estimated prevalence of diabetes was 12.4%, and of prediabetes was 38.1% [ 2 ]. Vascular complications of diabetes can lead to disability of diabetic patients and further affect the quality of life of patients [ 3 5 ]. A recent epidemiologic study has shown that cardiovascular disease (CVD) has climbed to the leading cause of mortality and morbidity in diabetes patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When interpreting blood glucose data, individual-level analysis encompasses single time point measurements, trends between two consecutive blood glucose measurements, and variability across multiple tests. At the group level, clustering patterns of blood glucose changes can be employed to describe collective modes of blood glucose control [ 5 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%